FAT LOSS RESOLUTION FOR MEMBERS OF THE INDONESIAN POLICE WHO EXPERIENCED OBESITY - Arifin, Mochamad (Universitas Negeri Surabaya, 2021)
This writing intens on solving the obesity problem that had been arround by some Republic Indonesian Police Force Members.The populations that will be used in this eriting or the Republic Indonesian Police Force Members that are getting into the obesity problems specially in Bandung, Lumajang, and Yogyakarta. The sample that will be used in this writing is the members of the police force œPolda DIY with the number 465 that are getting into overweight and about 85 are getting into the obesity problems. The sample making will use purposive sampling.The data processing that will produce the analysis that develop on many thoughts to get the sintesis from the problems that will be discussed. The program concept is a currative effort and rehabilitative that will be discussed by the writer with the target is the police force members that get the obesity problem, then they are will be given some treatments by applying the fatloss programe that the goal is to bring back the physical condition of the police that have obesity problem to the ideal physical fitness conditions.